Music as environment: movement cues as descriptors of musical experience - Damesón, Javier (2018)
Enactivism considers cognitive processes as originated in perceptually guided-actions; it sees cognitive activity as an outcome of the circular dynamic interactions between an organism and its environment (Schiavio et al., 2017), and the minds as inherent attributes of bodies in the world (Di Paolo et al., 2017). From this perspective, body movement might bring cues to explore self-organization phenomena of musical experience. We focused on physical movement properties employing two analytical frameworks: (a) impulsiveness based in Effort Laban`s model that relates low-level physical movements to mid-level expressive qualities; and (b) Recurrence Quantification Analysis (RQA) Entropy, from Dynamic Systems Theory.